Relaciones entre escarabajos (Coleoptera: Scarabaeidae) y nidos de tuza (Rodentia: Geomyidae): implicaciones biológicas y biogeográficas - Lobo, Jorge M.; Halffter, Gonzalo (Instituto de Ecología, A.C., 1994)
The relationship between Onthophagus hippopotamus Harold and gopher nests (Rodentia: Geomyidae) is confirmad. This relationship is not casual, since this beetle nests with the accumulated excrement of the rodent's burrows. The same relationship has been reportad for another closely related species of Onthophagus (0. coproides Horn) and it is very likely that it atso occurs in other species of the same complex. The existence of a guild of beetles which exploit rodent (and turtie) excrement in the burrows of the latter is also confirmad. Here, attention is drawn to the capture of two species of Aphodius along with O. hippopotamus, one of which is more associated with the Onthophagus, and even demonstrates cleptoparasitism on Onthophagus nests. The geographic distribution of Cratogeomys gophers is described, along with its overlap with the distribution of Onthophagus of the hippopotamus complex